Genome-wide association study identifies three new melanoma susceptibility loci - Barrett, Jennifer H; Iles, Mark M; Harland, Mark; Taylor, John C; Aitken, Joanne F; Andresen, Per Arne; Akslen, Lars A; Armstrong, Bruce K; Avril, Marie-Francoise; Azizi, Esther; Bakker, Bert; Bergman, Wilma; et al. (Nature genetics, 2011)
Timothy Bishop and colleagues of the GenoMEL Consortium report a genome-wide association study for melanoma, identifying three new susceptibility loci. We report a genome-wide association study for melanoma that was conducted by the GenoMEL Consortium. Our discovery phase included 2,981 individuals with melanoma and 1,982 study-specific control individuals of European ancestry, as well as an additional 6,426 control subjects from French or British populations, all of whom were genotyped for 317,000 or 610,000 single-nucleotide polymorphisms (SNPs). Our analysis replicated previously known melanoma susceptibility loci. Seven new regions with at least one SNP with P < 10 −5 and further local imputed or genotyped support were selected for replication using two other genome-wide studies (from Australia and Texas, USA). Additional replication came from case-control series from the UK and The Netherlands. Variants at three of the seven loci replicated at P < 10 −3 : an SNP in ATM (rs1801516, overall P = 3.4 × 10 −9 ), an SNP in MX2 (rs45430, P = 2.9 × 10 −9 ) and an SNP adjacent to CASP8 (rs13016963, P = 8.6 × 10 −10 ). A fourth locus near CCND1 remains of potential interest, showing suggestive but inconclusive evidence of replication (rs1485993, overall P = 4.6 × 10 −7 under a fixed-effects model and P = 1.2 × 10 −3 under a random-effects model). These newly associated variants showed no association with nevus or pigmentation phenotypes in a large British case-control series.